Students’ Perceptions Toward Quizizz as an Online Learning Media - Rahmawati, Sari (PANYONARA: Journal of English Education, 2021)
Indonesia adapted a new change in the education system since Pandemic COVID-19, especially for having online learning. The purpose of this study was to examine students' perceptions toward the use of Quizizz as an online learning media in English courses during the COVID-19 pandemic. The design of the study was descriptive qualitative. The subjects of the study were 89 Information Systems students of STMIK Jayanusa. The data was collected through a questionnaire on Google Forms and they were analyzed by using the Likert Scale. The study revealed that students responded to Quizizz use positively; they strongly agreed about the use of Quizizz in distance learning